The burgeoning field of sustainable investment: Past, present and future. (4th October 2022) - Beisenbina, Marzhan; Fabregat‐Aibar, Laura; Barberà‐Mariné, Maria‐Glòria; Sorrosal‐Forradellas, Maria‐Teresa
Abstract: The current concern with sustainability issues pervades all scientific fields. Sustainable investment is not an exception judging by the significant increase in the literature. This work provides an extensive up‐to‐date overview of studies on sustainable investment, revealing current trends, identifying gaps and future research topics. A total of 1091 documents are reviewed and bibliometric analysis is used with two approaches: data analysis and conceptual structure of the field. Additionally, a classification into 12 categories by topic is proposed. The results show that more than 40% of the publications belong to analysis of classical investment tools with a gradual evolution towards the concept of "green" instruments. Socially Responsible Investment (SRI) strategies have changed over time from "screening" to the current "best‐in‐class", "Environmental, Social and Governance (ESG) integration" and "impact investing." The results of the study are valuable for academics and practitioners, as they show the current state of knowledge, evolution paths and emerging topics.